GLOBALIZATION AND THE TRANSFORMATION OF CULTURAL AND LINGUISTIC IDENTITY IN THE TURKIC WORLD - Eshboyeva , Madina; Eshboyev , Temur (Effective scientific journals, 2026)
This study examines the impact of globalization on cultural values and linguistic identity within Turkic societies by drawing on sociological and cultural theories, particularly the concept of “liquid modernity,” to explore the interaction between traditional Turkic values and emerging global cultural patterns, while also highlighting the role of digital technologies, education systems, and communication platforms in shaping contemporary cultural identities; the findings indicate that globalization does not eliminate traditional values but instead fosters a process of adaptation in which historical traditions coexist with modern global influences, although the growing dominance of global languages and digital communication systems creates significant challenges for preserving and developing Turkic languages and cultural heritage, thereby emphasizing the need to strengthen linguistic cooperation, develop digital resources, and promote cultural education for sustainable cultural continuity.